X-23 (2010), volume 1 ebook - Liu, Marjorie (X-23 (2010), 2012)
Collects X-23 #1-6. X-23 has lived many lives, but none of them have ever felt right. Leaving the X-Men's island home of Utopia on a mission all her own, she's already found trouble. Even with the mutant thief Gambit at her side, her past haunts her. With new enemies rising, can X-23 trust herself not to succumb to her deadly ways?